Long-term survival after curative resection for pancreatic ductal adenocarcinoma – Surgical treatment. (September 2015) - Benassai, G.; Quarto, G.; Perrotta, S.; Furino, E.; Benassai, G.L.; Amato, B.; Bianco, T.; De Palma, G.; Forestieri, P.
Abstract: Introduction: Recent reports have demonstrated improvement in the 5-years serviva with resecate ductal adenocarcinoma. The aim of study is to determinate the factor influencing long-term survival after DCP. Materials and methods: We have critically reviewed a group of 85 patients how were admitted to our department with diagnosis of ductal adenocarcinoma of the head of pancreas between January 1974 and January 1998. Results: Patients were stratified according to stage using TNM classification; in stage I 31 patients with 5 T1aN0M0 disease, 11 patients with T1bN0M0 and 15 patients T2N0M0 disease. By contrast, in stage III 54 patients with 48 patients T2N1M0 and 6 patients with T3N1M0. Tumour size was recorded for 72 patients with a median of 3.8 cm. The R1 dissection was performed in 67 patients. The R2 resection was performed in 18 patients. In our series we verified and analysed the histopathologic features of 5 patients with 15-years survival (5.8%). The features regard age, male or female, tumours size, stage and positive lymph node resection. Discussion: We found a specifically subset of patients where the combination of prognostic factors, in particular, negative surgical margins R0, tumour size ≤30 mm and the absence of lymph node metastasis independently reduced the mortality indicating that earlier tumour detection and histologically curative resection are important factors contributing to long term survival and healing of ductal adenocarcinoma of the head of the pancreas.